In silico characterization of defense system hotspots in Acinetobacter spp. - Wenjing Yi; Ning Zhu; Zhihan Peng; Xiao Chu; Haotian Sun; Lei Song; Zhimin Guo; Arnab Pain; Zhaoqing Luo; Qingtian Guan (Communications Biology)
Abstract The bacteria-phage arm race drives the evolution of diverse bacterial defenses. This study identifies and characterizes the defense hotspots in Acinetobacter baumannii using a reference-free approach. Among 4383 high-quality genomes, we found a total of 17,430 phage defense systems and with 54.54% concentrated in 21 hotspots. These hotspots exhibit distinct preferences for different defense systems, and co-occurrence patterns suggest synergistic interactions. Additionally, the mobile genetic elements are abundant around these hotspots, likely facilitating horizontal transfer and evolution of defense systems. The number of hotspots increases in species phylogenetically closer to Acinetobacter baumannii, but the number of defense systems per hotspot varies due to particular selective pressures. These findings provide critical insights into the genetic organization of phage defense systems, contributing to a broader understanding of bacterial immunity and the evolutionary dynamics that shape Acinetobacter genomes. This knowledge lays the foundation for developing targeted interventions  to combat antibiotic resistance Acinetobacter baumannii.